The Impact of Legislative Criterea on the Judicial Conflit Idea - Abdelli, Sihem (Journal of Human Sciences, 2022)
Distributing the rules of judicial jurisdiction is considered as the criterion of the legislative standard, and any conflict of jurisdiction is classified as a mistake in the law, whether the error have occurred from the bodies of the ordinary judiciary, including the Supreme Court, or from the administrative judicial bodies, including the Council of State. On the same line of thought, it is proposed that the Dispute Court would be the authority that evaluates the work of the Supreme Court and the Council of State and ensure their respect for the law, and since the administration's judiciary is the responsible for the deviation from the legislative standard through its reliance on a judicial standard that includes the elements necessary to expand its jurisdiction, we suggest transferring jurisdiction by settling jurisdiction disputes to the Council of State, and transferring the dispute court to a the appeal in the administrative matter with a change of its name in proportion and accordance to its new duties.